Female pattern hair loss: A clinical and pathophysiological review - Ramos, Paulo Müller [UNESP]; Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2015)
Female Pattern Hair Loss or female androgenetic alopecia is the main cause of hair loss in adult women and has a major impact on patients’ quality of life. It evolves from the progressive miniaturization of follicles that lead to a subsequent decrease of the hair density, leading to a non-scarring diffuse alopecia, with characteristic clinical, dermoscopic and histological patterns. In spite of the high frequency of the disease and the relevance of its psychological impact, its pathogenesis is not yet fully understood, being infl uenced by genetic, hormonal and environmental factors. In addition, response to treatment is variable. In this article, authors discuss the main clinical, epidemiological and pathophysiological aspects of female pattern hair loss.
Keywords: Alopecia; Androgens; Epidemiology; Hair; Hair Follicle; Miniaturization; Women